(untitled) (Scientia Agropecuaria, 2025)
Changes in soil attributes following changes in management strategies in rice cultivation can alter soil quality, either positively or negatively. The aim of this study was to evaluate soil quality indicators, based on physical, chemical and microbiological soil attributes in Amazonian savanna under rice cultivation with different ages. The research was conducted in five areas under continuous rice cultivation during 1, 3, 8, 13, and 25 years, compared with local reference native vegetation. Soil samples were collected at 0-10 cm depth and evaluated for physical attributes such as texture and bulk density, chemical properties such as soil organic carbon, total nitrogen, exchangeable cations, available P, pH, CEC and C/N ratio; and microbiological attributes like microbial biomass carbon, soil microbial respiration, metabolic ratio and microbial coefficient. Acid phosphatase and urease activity were evaluated. With longer periods of time of rice cultivation, soil quality was enhanced with increasing soil fertility, increased soil organic carbon content and enzyme activity. The paddy soil indicators were sensitive to changes in rice cultivation and its duration. Acid phosphatase activity and available phosphorus increased with longer time of rice cultivation, indicating a possible conversion of inorganic into organic phosphorus forms, corroborated by increasing phosphatase activity. Microbiological (SMB-C, SBR, qMIC and qCO2) and biochemical (urease and acid phosphatase) indicators, as well as soil organic carbon and total nitrogen were highly sensitive to land use changes. Chemical and microbiological indicators are suitable for estimating paddy soil quality in lowland of Amazonian savanna.